Urban congestion and transport inefficiencies: Implications for livability in Dhaka City - Gazi Arafat Uz Zaman Markony; Jannateen Naoar Siena (Tamalanrea: Journal of Government and Development (JGD), 2025)
Urban livability refers to the degree to which urban environments foster long-term well-being and satisfaction among residents through adequate environmental quality, safety, accessibility, and sufficient social infrastructure, including housing, healthcare, education, green spaces, and transportation. This study assesses the impact of urban congestion and transport inefficiencies on livability in Dhaka City. It specifically explores indicators for measuring urban livability, analyzes the interrelationship between livability and transportation systems, and identifies associated challenges. Employing a qualitative approach, the research relies on secondary data from books, peer-reviewed journal articles, official reports, and reputable news portals. The findings indicate that urban congestion and transport inefficiencies significantly undermine livability in Dhaka. Rapid population growth exacerbates issues such as inadequate public transportation, missing essential infrastructure, and safety concerns. These problems cause substantial economic losses, impair public health through pollution and stress, and stem from overlapping institutional responsibilities and poor planning of housing and roadways. The study proposes targeted recommendations to address these challenges and enhance residents' quality of life in Dhaka City.